2009
DOI: 10.1021/ef800815b
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Analysis of Methane Hydrate Formation in Water-in-Oil Emulsions

Abstract: Water-in-oil emulsions are of particular interest concerning methane hydrate formation during crude oil production. The objective of this work is to understand the morphology of the hydrate/water drops in waterin-oil emulsions. Hydrogen nuclear magnetic resonance (NMR) is used to directly measure the formation of methane hydrates in water-in-oil emulsions. A 2 MHz NMR spectrometer is used to investigate the relationship between the drop size distributions of water-in-oil emulsions and methane hydrate formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 19 publications
0
21
0
1
Order By: Relevance
“…The presence of surface water on the particles can facilitate the agglomeration of hydrates during dissociation. From the studies of Aichele et al11 and Boxall et al,12 it can then be found that water droplet sizes affect both hydrate formation and agglomeration.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…The presence of surface water on the particles can facilitate the agglomeration of hydrates during dissociation. From the studies of Aichele et al11 and Boxall et al,12 it can then be found that water droplet sizes affect both hydrate formation and agglomeration.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, most drilling fluids in deepwater offshore drilling facilities, where hydrate plugging hazards may occur because of low seabed temperatures, are in forms of water‐in‐oil emulsions 3. Hence, understanding the characteristic of hydrate formation in water‐in‐oil emulsions has drawn much attention in recent years 4–14…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental results showed that the metastable boundary pressures increase with decreasing water-droplet sizes, but when the system pressure exceeds the metastable boundary pressure, hydrate formation occurs and the metastable state of the emulsion collapses. Aichele et al [15] used nuclear magnetic resonance to measure the formation of methane hydrates in water-in-oil emulsions and provided useful information regarding the relationship between drop size distributions and methane hydrate formation in emulsified systems. Boxall et al [16] performed methane hydrate formation/dissociation experiments from water-in-oil emulsions with three different size distributions.…”
Section: Introductionmentioning
confidence: 99%